The Crows among Hummingbirds: On Writing the Stories "The Party", "Silver Noon" and "Matryoshka" - Milica Popović 1991- (2020)
The following MA thesis is a work inspired by and based on a course in Creative Writing, taught by Dr. Anna Heiða Pálsdóttir at the University of Iceland in the spring of 2018. The thesis consists of three short stories, “The Party”, “Silver Noon” and “Matryoshka”, spanning almost 22500 words, as well as the exposition of the creative process, spanning roughly 3500 words. The three stories can be read as separate narratives, although their plots and protagonists are loosely connected. The main links between them are their shared setting, themes and key points of influence. The title of the thesis comes from “Matryoshka”, and describes the three protagonists who, despite their different socio-economic backgrounds, are all proverbial crows among hummingbirds: Lydia, an immigrant whose life begins to crumble as a result of sexual abuse in the workplace, Shaun, a troubled middle-aged man embarking on an unexpected quest on the last day of his life, Lucile, a rich heiress approaching middle age, caught in the midst of losing everything she thought of as permanent in her life. Two of the stories are set in the present, while one takes place in the relatively near future. This choice allowed for creative freedom of depicting a reality affected by climate change. The stories present the reader with explorations of unique inner worlds, while at the same time delving into the issues of femininity, grief, love, abuse, the future, and social injustice. The exposition of the creative process details my personal influences, themes and ambitions that shaped the stories into being. In brief notes, I explain the reasoning behind each characterization, narrative voice and setting, focusing primarily on their psychological and societal aspects. Together with the reader, I explore the ways in which these three stories are simultaneously similar, yet different from one another.